Screening of Muraya koenigii, Ocimum basilicum and Jasminum sambac for identification of coumarin and its derivatives - Mohd Shafri, Mohd Affendi; Abdul Salam, Muhammad Alif Nazruddin (2014)
Natural coumarins are of great interest due to their widespread pharmacological properties and this makes them attractive for further backbone derivatization and screening them as several novel therapeutic agents. In this study, the presence of coumarin in Muraya koenigii leaves, Ocimum basilicum leaves, and Jasminum sambac flowers, was screened. The samples were sourced locally and then subjected to extraction process using different concentration of methanol and ethanol for optimisation. Presence of coumarin was detected using thin layer chromatography (TLC) by comparing against commercial standards of coumarin. Results were further analysed by measuring the retention factor value (Rf) and estimating coumarin quantitatively using TLC Analyser. It was found that 95% ethanol extraction produced the best yield of coumarin. Derivatives of coumarin found in Muraya koenigii includes hydroxycoumarin and xanthotoxin, and in Ocimum basilicum includes hydroxycoumarin, psoralen and xanthotoxin, whereas Jasminum sambac yielded xanthotoxin only. TLC Analyser showed that the highest concentration of coumarin is contained in Muraya koenigii suggesting it as a plant candidate for coumarin-lead compound targeting.